Wheat rust research—then and now - SUBHASH C BHARDWAJ; PRAMOD PRASAD; OM P GANGWAR; HANIF KHAN; SUBODH KUMAR (The Indian Journal of Agricultural Sciences, 2016)
Wheat is an important constituent of human diet worldwide. India is the second largest producer of wheat in the world and wheat is directly related to the economic health of country. To meet the food requirements of the growing population, there is a need to increase wheat production. Wheat rusts caused by a fungus Puccinia species are the main biotic constraints in our efforts to sustain and boost production. Wheat rusts are historic and devastating pathogens worldwide. Their ability to spread aerially over the continents, production of infectious pustules geometrically in trillions and evolving new physiologic forms, makes the management of wheat rusts a very challenging task. To counter the threat of wheat rusts, efforts are going on worldwide. Identification of pathotypes, anticipatory breeding, evaluation for rust resistance and deployment of rust resistant cultivars is a time tested strategy to manage wheat rusts. There had been continuous efforts to increase the diversity for rust resistance. A list of more than 210 rust resistance genes and associated markers for many are available for the use of breeders. However, many of them have lost the effectiveness over the years. Introgression of rust resistance from rye and later on from other sources opened new vistas in research. However, the rust pathogens out smarted and new virulent pathotypes emerged which could overcome the novel rust resistance genes. Emergence of Ug 99 type of virulences threatened the cultivation of wheat in 40% of the world's acreage. DNA fingerprinting, sequencing of wheat and rust genomes were the milestone pieces of research in the 21st century. Efforts are still needed in studying the perpetuation of wheat rusts, epidemiology and inventing next generation techniques to break the yield barriers and manage wheat rusts. Role of Berberis chinensis, B. holstii, B. koreana and B. vulgaris as alternate hosts to P. striiformis (yellow rust of wheat) was an important discovery in this respect. Consolidated information on wheat rust research conducted over the years has been reviewed in this publication.